(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The objectives of this study were to: 1) to study the problems and requirements related to information systems for management for health tourism in Ranong province. 2) to develop an information system for health tourism management in Ranong province, and 3) study the factors affecting the adoption of information systems for health tourism management in Ranong province. This research is a mixed research method. The requirement was gathered 5 health tourism entrepreneurs and 25 tourists for a total of 30 people by interview. The results from the interviews were used to develop an information system for health tourism management. After that, a study on study the factors affecting the adoption of information systems for health tourism management was conducted using a questionnaire as the research instrument to collect data from 385 tourists. The inferential statistical analysis that was the multiple regression. The research findings reveal that the operators still lack information systems or technologies related to health tourism management. There is a need for an application to be used for promoting health tourism in Ranong province. Based on these findings, The researchers developed an information system and tested its acceptance. The results of the study of factors affecting the adoption of information systems for health tourism management found that there are 4 independent variables: The most predictable variables are Attitude Towards Use, followed by Perceived Usefulness, Behavioural Intention to use, and Perceived Ease of Use respectively. The study produced an innovative information system for managing health tourism and expanding the set of knowledge and concepts on the technology acceptance model. The findings of this study can serve as a valuable resource for devising strategic plans to enhance Health Tourism Management